The influence of price value on purchase intention among patients with chronic diseases in medical e-commerce during the COVID-19 pandemic in China - Han, Linlin; Han, Xu (Frontiers in Public Health, 2023)
Background: During the COVID-19 pandemic, medical e-commerce (MEC) has provided a way for patients with chronic diseases to purchase drugs online to maintain social distancing, decrease the risk of infection and community transmission, and relieve the burden on medical resources. Therefore, research which seeks to elucidate the drivers of purchase intention (PI) among patients with chronic diseases in MEC is vital. This study extended the theory of planned behavior (TPB) by integrating the price value (PV) variable into the original TPB framework and explored the effect of PV on patients' PI in MEC during the coronavirus pandemic. Methods: Empirical data was gathered from 414 Chinese participants. Structural equation modeling was applied to explore the mechanism of chronic patients’ PI in MEC. In addition, this study also estimated the moderating effect of gender, income, and region and the mediating role of attitude (ATT), subjective norm (SN), and perceived behavioral control (PBC) between PV and PI. Results: Patients' PI in MEC is significantly affected by ATT, SN, and PBC. PV delivers significant influence on ATT, SN, PBC, and PI, with PV having the strongest effect on ATT. Gender, income, and region can significantly moderate the relationship between PV and ATT. Conclusion: These findings can contribute to design targeted interventions to increase the adoption of MEC for patients with chronic diseases, decrease infection rates, and alleviate the strain on medical resources in the COVID-19 era.